(untitled) (Journal of the College of Basic Education, 2023)
The process of artistic production assumes the borrowing of a wide range of plant and animal formsAs well as the imaginary forms that are formed by nature according to realistic formal relationshipsPhotographing it according to considerations that give its formal characteristics ideological, social and spiritual influences. The process of employing forms may adopt the mechanisms of formal metaphor and the mechanism of this transformationShapes in a way that allows rediscovering their expressive energy and the possibility of employing them withinAn integrated intellectual system that is consistent with the intellectual reality and with the requirements of artistic production. Perhaps a metaphorShapes and their transformation to ensure their aesthetic use is what has become clear over a long periodFrom the artistic production, the idea of ​​modifying forms, especially the vegetable ones, was associated with the mechanisms of metaphorArtistic formalism and with the technique of employing these forms within the hierarchy of artistic production by adopting a factorThe time that prepares different treatments for the form of the difference in the social and intellectual influence. The problem of the current study is based on the study of borrowing botanical forms and their use inThe implementation of ceramic dishes and formal processing mechanisms that show a range of products thatThey vary in terms of the mechanism of transformation and metaphor, which produces a group of artistic stylesWith different implementation methods and different places, which distinguished the ceramic productions from othersWhich works within the prevailing intellectual system that distinguished ceramic productions in artistic productionIslam in general.